2008
DOI: 10.1002/adfm.200700609
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of Diatom Frustules for Nanotechnology: Tethering Active Biomolecules

Abstract: Diatoms are single‐celled microalgae with rigid walls (frustules) composed of amorphous silica. The intricate 3D microstructure of diatoms results in a high surface area formed by myriad pores and channels. The combination of the silica chemistry of the frustule coupled with the high surface area makes it particularly suitable for applications such as microscale total analysis systems. Here it is demonstrated that the diatom frustule can be chemically modified for the attachment of antibodies, and that the att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
77
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 9 publications
0
77
0
2
Order By: Relevance
“…Losic and colleagues 8,9 have pursued the idea of using diatom biosilica as a biocarrier for applications in oral and implant drug delivery, and have demonstrated their potential to replace synthetic silica-based materials. Chemical functionalization allows for the tailoring of drug binding and release properties 10,11 , and for the covalent immobilization of functional antibody molecules to diatom silica 12,13 . Combining both antibody attachment and drug loading on the same diatom silica particle should allow for targeted delivery of the drug to specific locations in vivo, for example, to cancer cells.…”
mentioning
confidence: 99%
“…Losic and colleagues 8,9 have pursued the idea of using diatom biosilica as a biocarrier for applications in oral and implant drug delivery, and have demonstrated their potential to replace synthetic silica-based materials. Chemical functionalization allows for the tailoring of drug binding and release properties 10,11 , and for the covalent immobilization of functional antibody molecules to diatom silica 12,13 . Combining both antibody attachment and drug loading on the same diatom silica particle should allow for targeted delivery of the drug to specific locations in vivo, for example, to cancer cells.…”
mentioning
confidence: 99%
“…The absorbability and PL characteristics of modified frustules have an enhancement: PL spectrum sensitive to gases at 1 ppm. In 2009, Gale et al [25] found that PL can be affected by the biomass attached to the frustules, and used frustules for protein detection a year after Townley et al [24] first bound proteins onto frustules. With the technique of protein binding, Lin et al [27] used frustules with uniform pores as biocarriers for electrochemical detection.…”
Section: Potential Of Diatom Frustules In Device Applicationmentioning
confidence: 99%
“…The resulting new theories and techniques have found wide application, leading to the formation of a new interdisciplinary area of research called diatom-based bio-nanotechnology (or diatom nanotechnology) [16][17][18][19][20][21]. The potential for diatoms in device applications, such as high-sensitivity gas sensors [22], drug delivery devices [23], biocarriers for biosensors [24][25][26][27], micro-filters [12,28], solar cells, battery electrodes and electroluminescent display devices [19] has been examined. However, the direct use of original frustules limits the function of any practical diatom based device.…”
mentioning
confidence: 99%
“…Importantly, the ability to manipulate the frustules on a large scale, combined with simple arraying techniques 20 , may enable the development of practical, real-world applications using diatoms. However, despite the promise of the use of diatom frustules in a variety of areas, the unique properties of diatoms have typically only been studied on the scale of a single diatom frustule (requiring only individual diatom alignment) [6][7][8][10][11][12][13][14][15][16] or as bulk materials (requiring no significant alignment) 17 .…”
Section: Introductionmentioning
confidence: 99%
“…To date, the use of diatoms as key components in a variety of application areas has been reported. For example, in applications to sensing technology, diatoms have been employed as the sensing components in immunoassays and gas sensors [10][11][12][13][14] . Furthermore, in work by Lin et al 11 , diatom frustules have been employed in electrochemical impedance sensing and have been found to significantly improve performance, including sensitivity, response time, and dynamic range, compared with existing approaches.…”
Section: Introductionmentioning
confidence: 99%